Mechanical adhesion strength on pine wood surfaces planed and bonded by pvac adhesives - Biazzon, João Carlos [UNESP]; De Araujo, Victor Almeida; Alves, Paulo Roberto Gomes [UNESP]; Morales, Elen Aparecida Martines [UNESP]; Gonçalves, Marcos Tadeu Tibúrcio [UNESP]; De Domenico Valarelli, Ivaldo [UNESP] (FapUNIFESP (SciELO), 2019)
This study aimed to analyze the performance of bonded joints of the Pinus elliottii wood species with the use of two commercial adhesives based on vinyl polyacetate (PVAc) with different physical characteristics and chemical composition, both tested on water diluted and undiluted modes. The surfaces of wood specimens were machined in discordant milling process. A wood thickness planer with headstock of four semi-fast car-bon steel sharpened knives based on Cr-Ni-V was used. This machine was prepared to operate with cutting speed (Vc) of 30.18 ms-1 and feed rate of wood (Vf) of 11.75 m.min-1, resulting in an feed rate per tooth (fz) of 0.56 mm. The specimens were prepared for tests of resistance to rupture in the glue line by the shear stress efforts according to the ABNT NBR 7190:1997 standard. In order to specimen preparation, the parts were randomly glued in relation to the formation plans of the wood growth rings. The following average values of shear strength in the glue line (fv0) obtained in diluted and undiluted forms were, respectively, PVAc - M: 6.52 and 6.49 MPa; PVAc - H: 5.86 and 5.15 MPa. In relation to the shear stress at the glue line, it was con-cluded that both adhesives in diluted form with 33.33% of water resulted in higher adhesion strength in com-parison to the original formulation, whereas the diluted adhesive type M provided an increasing of 21.01% regarding the undiluted adhesive of type H.
Resistência mecânica adesão em superfícies de madeira de pinus aplainadas e unidas por adesivos PVAc
Keywords: Glue line; Machining; Shear strength; Wood